2018
DOI: 10.1172/jci.insight.121560
|View full text |Cite
|
Sign up to set email alerts
|

IL-33 modulates inflammatory brain injury but exacerbates systemic immunosuppression following ischemic stroke

Abstract: Stroke triggers a complex inflammatory process in which the balance between pro- and antiinflammatory mediators is critical for the development of the brain infarct. However, systemic changes may also occur in parallel with brain inflammation. Here we demonstrate that administration of recombinant IL-33, a recently described member of the IL-1 superfamily of cytokines, promotes Th2-type effects following focal ischemic stroke, resulting in increased plasma levels of Th2-type cytokines and fewer proinflammatory… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
41
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 50 publications
(41 citation statements)
references
References 57 publications
(62 reference statements)
0
41
0
Order By: Relevance
“…Our data are consistent with a role of AIM2 in these brain resident cells and regions, but we cannot exclude circulating leukocytes as another possible cell mediating the pro-inflammatory actions of AIM2 in the brain in chronic hypoperfusion. Leukocytes contribute to other forms of brain injury and neurodegeneration 5759 and their infiltration from the circulation would be expected in association with reduced blood-brain barrier integrity and blood vessel density known to occur in hypoperfusion-induced VaD 60 . However, in this study we have not assessed the role of leukocyte infiltration and related neutrophil extracellular traps (NETs), known as NETosis, as a potential source of AIM2 ligand.…”
Section: Discussionmentioning
confidence: 99%
“…Our data are consistent with a role of AIM2 in these brain resident cells and regions, but we cannot exclude circulating leukocytes as another possible cell mediating the pro-inflammatory actions of AIM2 in the brain in chronic hypoperfusion. Leukocytes contribute to other forms of brain injury and neurodegeneration 5759 and their infiltration from the circulation would be expected in association with reduced blood-brain barrier integrity and blood vessel density known to occur in hypoperfusion-induced VaD 60 . However, in this study we have not assessed the role of leukocyte infiltration and related neutrophil extracellular traps (NETs), known as NETosis, as a potential source of AIM2 ligand.…”
Section: Discussionmentioning
confidence: 99%
“…There is an increasing evidence that induction of Th2-type immune response has neuroprotective effects following stroke by limiting progression of the ischemic infarct [49][50][51][52]. However, repetitive administration of M2 cytokines after ischemic stroke can enhance the post-stroke immunosuppression, thereby facilitating bacterial infections and increasing mortality [53,54]. In our study, we used a single dose of IL-13 in a pMCAo model that produces strictly cortical lesions.…”
Section: Discussionmentioning
confidence: 99%
“…We recently found that the IL‐1 family cytokine IL‐33 made by astrocytes physiologically regulates microglial synapse elimination . This homeostatic function is distinct from its reparative role in the context of injury , Alzheimer's disease and ischemic stroke . Another IL‐1 family member, IL‐18, is also locally expressed in the brain, including in the emotion and threat regulating centers in the basolateral amygdala and has been proposed to mediate behavioral responses to chronic stress .…”
Section: Signaling Molecules Regulating Cns Immunitymentioning
confidence: 99%